Alvimopan, a peripherally acting mu-opioid receptor (PAM-OR) antagonist for the treatment of opioid-induced bowel dysfunction: Results from a randomized, double-blind, placebo-controlled, dose-finding study in subjects taking opioids for chronic non-cancer pain - Webster, Lynn; Jansen, Jan Peter; Peppin, John; Lasko, Ben; Irving, Gordon; Morlion, Bart; Snidow, Jerry; Pierce, Amy; Mortensen, Eric; Kleoudis, Christi; Carter, Eric (Pain (Amsterdam), 2008)
Our objective was to investigate the efficacy and safety of alvimopan, a peripherally acting mu-opioid receptor (PAM-OR) antagonist, in subjects with non-cancer pain and opioid-induced bowel dysfunction (OBD), and to identify at least one treatment regimen that improves OBD. Following a 2-week baseline period, 522 subjects reporting <3 spontaneous bowel movements (SBMs)/week (with ⩾25% accompanied by a sensation of incomplete evacuation, straining, or lumpy hard stools), requiring analgesia equivalent to ⩾30 mg oral morphine/day were randomized to alvimopan 0.5 mg twice daily (BID), 1 mg once daily (QD), 1 mg BID, or placebo for 6 weeks. Compared with placebo, there was a statistically and clinically significant increase in mean weekly SBM frequency over the initial 3 weeks of treatment (primary endpoint) with alvimopan 0.5 mg BID (+1.71 mean SBMs/week), alvimopan 1 mg QD (+1.64) and alvimopan 1 mg BID (+2.52); P < 0.001 for all comparisons. Increased SBM frequency and additional treatment effects, including improvements in symptoms such as straining, stool consistency, incomplete evacuation, abdominal bloating/discomfort, and decreased appetite, were sustained over 6 weeks. The most frequently reported adverse events were abdominal pain, nausea, and diarrhea, occurring more frequently in the higher dosage groups. The alvimopan 0.5 mg BID regimen demonstrated the best benefit-to-risk profile for managing OBD with alvimopan in this study population, with a side effect profile similar to that of placebo. There was no evidence of opioid analgesia antagonism. Competitive peripheral antagonism of opioids with alvimopan can restore GI function and relieve OBD without compromising analgesia.